Model Problem Based Learning dengan Pendekatan Culturally Responsive Teaching terhadap Keterampilan Berpikir Kritis Siswa SD - Safirah, Adita Dwi; Ningsih, Yuni Fitriyah; Suhartiningsih, Suhartiningsih; Masyhud, M. Sulthon; Hutama, Fajar Surya (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2024)
The impact of the Fourth Industrial Revolution era demands students to possess critical thinking skills to keep up with technological advancements. However, a considerable number of students exhibit low levels of critical thinking skills. The aim of this research is to analyze the impact of the Problem-Based Learning model with a Culturally Responsive Teaching approach on students’ critical thinking skills. This study employs a quasi-experimental research design using the Nonequivalent Control Group Design. Instruments used to measure critical thinking skills include pretests and posttests in the form of essay questions. Data analysis is conducted using descriptive techniques and t-tests. The research findings indicate that the implementation of the Problem-Based Learning model with a Culturally Responsive Teaching approach has a positive impact on students’ critical thinking skills. This is evident in the final results of the experimental group, where the average score is 85.72 with a total of 28 students (N). In contrast, the control group has an average score of 58.44 with a total of 30 students (N). The T-test results show that the calculated t value is greater than the t table (10.933 > 1.672) and a significance value (sig.) of 0.000 < 0.05, leading to the rejection of the Null Hypothesis (Ho) and acceptance of the Alternative Hypothesis (Ha). Overall, these findings confirm the significant influence of implementing the Problem-Based Learning model with a Culturally Responsive Teaching approach on students’ critical thinking skills.